Measurement of the lifetime difference in the Bs0 system - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2005)
We present a study of the decay Bs0â†'J/ÏÏ•. We obtain the CP-odd fraction in the final state at time zero, Râš¥=0.16Â±0.10(stat)Â±0.02(syst), the average lifetime of the (Bs0, BÂs0) system, Ï.,Â(Bs0)=1.39- 0.16+0.13(stat)-0.02+0.01(syst)ps, and the relative width difference between the heavy and light mass eigenstates, ÎÎ/ ÎÂâ‰¡(ÎL-ÎH)/ ÎÂ=0.24-0.38+0.28(stat)-0.04+0.03(syst). With the additional constraint from the world average of the Bs0 lifetime measurements using semileptonic decays, we find Ï.,Â(Bs0)=1.39Â±0.06ps and ÎÎ/ÎÂ=0.25-0.15+0.14. For the ratio of the Bs0 and B0 lifetimes we obtain Ï.,Â(Bs0)Ï.,(B0)=0. 91Â±0.09(stat)Â±0.003(syst). © 2005 The American Physical Society.